Konsep Diri dan Tuhan dalam Perspektif Filsafat Islam: Studi Hadist “Man 'Arafa Nafsahu 'Arafa Rabbahu” - Kerwanto, Kerwanto; Indriani, Fera (Universitas Muhammadiyah Tangerang, 2025)
This research explores the concept of the self in Islamic philosophy, revealing its critical role in understanding the divine. It highlights the perspectives of key philosophers such as Al-Farabi, Ibn Sina, and Ibn Arabi, who collectively emphasized that self-knowledge is essential to achieving a deeper understanding of God. Al-Farabi's focus on active intelligence illustrates the progressive nature of intellectual growth, while Ibn Arabi's insight into the role of the heart in spiritual experience underscores the importance of experiential knowledge. The hadith “Man 'Arafa Nafsahu 'Arafa Rabbahu” encapsulates the idea that self-awareness is the gateway to divine understanding, bridging philosophical inquiry with spiritual practice. This synthesis of thought illustrates that self-exploration in Islamic philosophy is a holistic effort, integrating intelligence, spirituality, and ethical life, which ultimately guides individuals towards a deep understanding of their relationship with the Divine.